Socio-Economic benefits of the KKK and it's effects on the political trust of the beneficiaries - Acena, Leah E.
Results of the study showed that the socio-economic benefits of the KKK to its beneficiaries have inconsistent effects on the degree of the political trust of the respondents towards the government. In cases where the socio-economic benefits of the KKK give the respondents greater capacity to pay their rentals and enable them to enjoy luxuries such as buying of personal things like the cosmetics and engaging in recreations such as movie watching, the socio-economic benefits showed a correlation to the degree of the political trust of the respondents towards the government. As shown by the results of the study, those who were helped by the KKK to pay their rentals and those who are enjoying luxuries which they were not enjoying before their involvement in the KKK project, have greater tendencies to "strongly trust" the government than those who were not helped by the KKK pay their rentals and to engage in luxuries due to their inadequacy of their income from the KKK to meet those expenses. , However, the other socio-economic benefits such as the help given by the respondents' income from the KKK in maintaining their homes and the acquisition of appliances did not have considerable effects on the degree of the political trust of the respondents because majority of those who are availing and those who are not availing of the benefits have tendency to "strongly trust" the government. The results showed that the income levels of the respondents do not determine the degree of their political trust towards the government. As shown by the results of the study, all income levels have tendencies to "strongly trust" the government. Rather, the degree of the political trust is determined by the respondents' general belief that the government is capable to help the people attain socio-economic development and that one sign of this, as most of the respondents have seen it, is the government's implementation of the KKK-- a project that had provided jobs for the jobless.